Epidemiologic analysis of the monkeypox incidence based on genetic and ecological characteristics of the new isolates - Kravchenko, H. V.; Krupiei, K. S.; Крупєй, Кристина Сергіївна (Запоріжжя : ЗМАПО, 2022)
Aim: to systematize epidemiological information on the monkeypox virus, taking into account the genetic features of the variants circulating in the current outbreak (2022), and give recommendations based on the ecological features of the virus.
Keywords: тези доповідей